Characterization of occult hepatitis c virus (hcv) infection among hemodialysis patient - Abdul Rahman, Siti Nurul Fazlin; Hamzah, Hairul Aini; Mustafa, Imad Al-Deen; Hasmoni, Mohamed Hadzri (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
The existence of new entity called occult hepatitis C virus (HCV) has become a raising and escalating concern among healthcare professionals worldwide. It is defined by the presence of viral RNA in liver and/or peripheral blood mononuclear cells (PBMCs) within non HCV-infected patients. Previous study had shown the occult HCV is infectious and capable of transmitting the virus to another host. Till today, HCV infection remains common among hemodialysis patients despite having the best preventive plans. Because of this, there is a significant concern about the source of viral transmission. The aim of the study was to identify and characterize occult HCV infection in PBMC sample of hemodialysis patients. This was an observational and cross sectional study.